2011
DOI: 10.1002/ana.22236
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide phosphoribosyltransferase protects against ischemic stroke through SIRT1‐dependent adenosine monophosphate–activated kinase pathway

Abstract: Our findings reveal that Nampt protects against ischemic stroke through rescuing neurons from death via the SIRT1-dependent AMPK pathway and indicate that Nampt is a new therapeutic target for stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
285
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(292 citation statements)
references
References 32 publications
7
285
0
Order By: Relevance
“…A recent study reports that nicotinamide phosphoribosyltransferase (Nampt), the rate-limiting enzyme in mammalian NAD biosynthesis, protects against ischemic stroke in rodents (53). Given that Nampt and Nmnat1 are in the NAD-synthesis pathway, they may share similar mechanistic pathways in protection against ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reports that nicotinamide phosphoribosyltransferase (Nampt), the rate-limiting enzyme in mammalian NAD biosynthesis, protects against ischemic stroke in rodents (53). Given that Nampt and Nmnat1 are in the NAD-synthesis pathway, they may share similar mechanistic pathways in protection against ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that increases in Nampt expression increase NAD þ levels and the NAD þ /NADH ratio. 6,14,15 Since our previous experiments identified PKCe as a regulator of mitochondrial Nampt, we now wanted to determine whether PKCe has a role in regulating mitochondrial levels of NAD þ , NADH, and the NAD þ /NADH ratio in the cortex.…”
Section: Protein Kinase C Epsilon Is a Major Regulator Of Amp-activatedmentioning
confidence: 99%
“…Nicotinamide phosphoribosyltransferase therefore plays a key role in the regulation of energy metabolism and stress responses. Previous studies indicated that lentivirus-mediated NAMPT overexpression is neuroprotective against ischemic brain injury, 11 while genetic deletion of NAMPT exacerbates ischemic brain injury. 12 Specifically, Wang and colleagues reported that NAMPT upregulation is part of a natural stress response to ischemic injury and that it protects gray matter through sirtuin 1-dependent modulation of the adenosine monophosphate-activated kinase pathway.…”
Section: Introductionmentioning
confidence: 99%